Difficult secularity: Talmud as symbolic resource - Zittoun, Tania (Outlines. Critical Practice Studies, 2006)
Religious systems are organised semiotic structures providing people with values and rules, identities, regularity, and meaning. Consequently, a person moving out of a religious system might be exposed to meaning-ruptures. The paper presents the situation of young people who have been in Yeshiva, a rabbinic high-school, and who have to join secular university life. It analyses the changes to which they are exposed. On the bases of this case study, the paper examines the following questions: can the religious symbolic system internalised by a person in a religious sphere of experience be mobilised as a symbolic resource once the person moves to a secular environment? If yes, how do religious symbolic resources facilitate the transition to a secular life? And if not, what other symbolic and social resources might facilitate such transitions?